1975
DOI: 10.1002/app.1975.070191019
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mixing on the modes of dispersion and rheological properties of two‐phase polymer blends in extrusion

Abstract: SynopsisAn experimental study was carried out to investigate the effect of mixing on the state of dispersion and rheological properties in the two-phase flow of polymer blends. For the study, blends of polystyrene and polypropylene were used, and two mixing devices were employed a single-screw extruder combined with a "static mixer," and a twin-screw compounding machine. Materials of various blending ratios were extruded a t a constant temperature (200'C) through a capillary die having an LID ratio of 20 (D = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(39 citation statements)
references
References 11 publications
3
36
0
Order By: Relevance
“…The viscosities that Lepoutre [40] obtained for the PP/EVOH blend system were lower than the respective homopolymer viseosities, which led to designating the blends as negatively deviating. This deviation from the additivity rule has also been observed for other blend systems [27,28,29,39].…”
Section: Pp/evoh and Pp/mapp/evoh Blendsmentioning
confidence: 74%
See 2 more Smart Citations
“…The viscosities that Lepoutre [40] obtained for the PP/EVOH blend system were lower than the respective homopolymer viseosities, which led to designating the blends as negatively deviating. This deviation from the additivity rule has also been observed for other blend systems [27,28,29,39].…”
Section: Pp/evoh and Pp/mapp/evoh Blendsmentioning
confidence: 74%
“…Han [29] PS/PP Danesi [30] PP/EP Vinogradov POM/CPA [31][32][33] Krasnikova PP/PS [34] Tsebrenko POM/CEVAc [35] Lyngaae-PE/PP Jorgensen À<l,""l À""l Table 2.6). Micrographs of samples produced under controlled processing conditions (blow-molded container and extruded sheet) showed that the nylon material was not distributed as a homogeneous, unifcrm blend, ~ut rather as multiple layers, or platelets, along the wall thickness.…”
Section: B) Capillary Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Blends of polypropylene (PP) for improving properties suited to some specific application were extensively studied with a large number of polymers, including polyethylene, [1][2][3][4][5] polycarbonate, 6 polyamide, [7][8][9][10] polystyrene, 11,12 acrylonitrile-butadienestyrene (ABS), 13 ethylene-vinyl acetate (EVA), 14 elastomers. [15][16][17][18] However, the blends of PP and PP grafted with maleic anhydride (PP-g-MA) seem to have been scantily studied.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5 indicates the correlation between e and the apparent shear stress Tw for the P-E and P-M systems. In this case, v~ was used instead of because, as pointed out by Han [10], the variation in ? is not continuous due to the formation of discontinuous phases of micro-structure between two polymers.…”
Section: Flow Behaviormentioning
confidence: 99%